Upper, middle, and lower CALYX accesses for prone percutaneous nephrolithotomy: a comparative study - Ammar Fadil Abid; Samer Sabah Omar (Journal of the Pakistan Medical Association, 2024)
Objective: To compare upper, middle and lower calyceal accesses for prone percutaneous nephrolithotomy regarding stone-free rates, residual stones, haemoglobin drop and fluoroscopic time. Method: The prospective comparative clinical study was conducted from September 2018 to March 2021 at Al-Yarmouk Teaching Hospital, Baghdad, Iraq, and comprised patients of either gender aged 18-78 years with renal stones treated with percutaneous nephrolithotomy. They were divided into three groups on the basis of calyx access: upper calyx G1, mid-calyx G2, and lower calyx G3. Procedure-related parameters, such as fluoroscopic time, stone-free rates and haemoglobin drop, were analysed in detail. Patients were followed up within 1-week post-surgery through complete blood count, ultrasound and computerised tomography. Data was analysed using SPSS 27. Results: Of the 151 patients with a mean age of 46.01±14.7 years, 89(58.9%) were males and 62(41.1%) were females. There were 63(41.7%) patients in G1, 38(25.2%) in G3 and 50(33.1%) in G3. The diameter of renal stones ranged from 20-60mm. There were 45(71.4%) patients with stone-free outcome in G1, 22(57.9%) in G2 and 37(74%) in G3 (p>0.05). There was no significant difference in the mean haemoglobin drop among the groups (p>0.05). Conclusions: No significant intergroup difference was observed in terms of access in the sequelae regarding residual stone and haemoglobin drop. Key Words: Nephrolithotomy, Percutaneous, Blood Cell, Hemoglobins, Tomography